Glycan-Modified Melanoma-Derived Apoptotic Extracellular Vesicles as Antigen Source for Anti-Tumor Vaccination - Horrevorts, Sophie K; Stolk, Dorian A; Ven, Rieneke van de; Hulst, Myrthe; Hof, Bert van Het; Duinkerken, Sanne; Heineke, Marieke H; Ma, Wenbin; Dusoswa, Sophie A; Nieuwland, Rienk; Garcia-Vallejo, Juan J; Loosdrecht, Arjan A van de; et al. (Cancers, 2019)
Tumors that lack T cell infiltration are less likely to respond to immune checkpoint inhibition and could benefit from cancer vaccination for the initiation of anti-tumor T cell responses. An attractive vaccine strategy is in vivo targeting of dendritic cells (DCs), key initiators of antigen-specific T cell responses. In this study we generated tumor-derived apoptotic extracellular vesicles (ApoEVs), which are potentially an abundant source of tumor-specific neo-antigens and other tumor-associated antigens (TAAs), and which can be manipulated to express DC-targeting ligands for efficient antigen delivery. Our data demonstrates that by specifically modifying the glycocalyx of tumor cells, high-mannose glycans can be expressed on their cell surface and on extracellular vesicles derived after the induction of apoptosis. High-mannose glycans are the natural ligands of dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), a dendritic cell associated C-type lectin receptor (CLR), which has the ability to efficiently internalize its cargo and direct it to both major histocompatibility complex (MHC)-I and MHC-II pathways for the induction of CD8 and CD4 T cell responses, respectively. Compared to unmodified ApoEVs, ApoEVs carrying DC-SIGN ligands are internalized to a higher extent, resulting in enhanced priming of tumor-specific CD8 T cells. This approach thus presents a promising vaccination strategy in support of T cell-based immunotherapy of cancer.